MULTIFARIOUS ACTIONS OF DIETARY FLAVONOIDS – IMPLICATIONS IN CANCER AND CATARACT - DURGA.M,; NATHIYA.S,; DEVASENA.T, (International Journal of Pharma and Bio Sciences, 2014)
Flavonoids are widely present in fruits and vegetables. Different categories of flavonoids such as flavonals, flavones, flavonones, isoflavone, catechin, anthocyanin and isoflavone are present in plants. It has been discovered that they have many beneficial actions on body cells by enhancing the activity of many enzyme systems. The aim of this present review is to summarize the significant multifunctional and biological activities of flavonoids such as anti-allergic, anti-toxic, anti-microbial, anti-cataract and anti-cancer activity and to present the recent advancements in the pharmacological and chemical properties of flavonoids.